2004
DOI: 10.1530/rep.1.00104
|View full text |Cite
|
Sign up to set email alerts
|

Are Src family kinases involved in cell cycle resumption in rat eggs?

Abstract: The earliest visible indications for the transition to embryos in mammalian eggs, known as egg activation, are cortical granules exocytosis (CGE) and resumption of meiosis (RM); these events are triggered by the fertilizing spermatozoon through a series

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
58
1

Year Published

2005
2005
2009
2009

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(62 citation statements)
references
References 55 publications
3
58
1
Order By: Relevance
“…Expression of Fyn, a member of Src kinase family (SFKs), is demonstrated and its activity is detected in rat eggs, which represents the first demonstration of a PTK in mammalian eggs (Talmor et al 1998). Furthermore, other members of SFKs, including Src and Yes, were detected in rat eggs (Talmor-Cohen et al 2004). In the present study, for the first time, we detected Pyk2 expression in mammalian eggs.…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…Expression of Fyn, a member of Src kinase family (SFKs), is demonstrated and its activity is detected in rat eggs, which represents the first demonstration of a PTK in mammalian eggs (Talmor et al 1998). Furthermore, other members of SFKs, including Src and Yes, were detected in rat eggs (Talmor-Cohen et al 2004). In the present study, for the first time, we detected Pyk2 expression in mammalian eggs.…”
Section: Discussionsupporting
confidence: 59%
“…Protein tyrosine kinases (PTKs) are essential in extracellular signaling and actin cytoskeleton organization. A small group of PTKs have been identified in eggs of invertebrates, lower vertebrates and some mammals, and inhibitor studies have suggested that they are involved in egg activation (Sato et al 2000, Runft et al 2002, Talmor-Cohen et al 2004. It has been suggested that protein tyrosine phosphorylation may be implicated in the regulation of mouse oocyte maturation.…”
Section: Introductionmentioning
confidence: 99%
“…In cases of spontaneous activation none of these indicators of activation were found. Interestingly, in ionomycin-activated rat eggs, it was demonstrated that resumption of meiosis and PN development were significantly hindered by Src family tyrosine kinase inhibitors, while cortical granule exocytosis was not (43). Another study in mouse demonstrated that during sequential fractionation of freeze-thaw sperm extracts, the ability to support pronuclear formation was lost before Ca 2ϩ -releasing ability (44).…”
Section: Discussionmentioning
confidence: 99%
“…Inhibitor studies performed in oocytes from mouse and rat have implicated Src-family PTKs in events required for MII resumption following parthenogenetic activation (Sette et al 2002, Talmor-Cohen et al 2004a. After fertilization, PTK inhibitors have been shown to block zygote development during or just prior to DNA synthesis resulting in an arrest of development prior to the two-cell stage (Besterman & Schultz 1990, Jacquet et al 1995.…”
Section: Role Of Src-family Kinases During Zygotic Developmentmentioning
confidence: 99%
“…For example, while mammalian eggs express Fyn, Yes, and in some cases, Src (Talmor et al 1998, Talmor-Cohen et al 2004a), the results of two different studies indicate that these kinases are not required for the unique sperm-induced calcium oscillations (Kurokawa et al 2004a, Mehlmann & Jaffe 2005, which trigger egg activation in mammals (Carroll 2001). Instead, these calcium oscillations are triggered directly by a sperm-borne phospholipase that does not require PTK regulation (Cox et al 2002).…”
Section: Introductionmentioning
confidence: 99%